A Novel Function of MUC18 - Wu, Qun; Case, Stephanie R.; Minor, Maisha N.; Jiang, Di; Martin, Richard J.; Bowler, Russell P.; Wang, Jieru; Hartney, John; Karimpour-Fard, Anis; Chu, Hong Wei (The American journal of pathology, 2013)
Bacterial infection plays a critical role in exacerbations of various lung diseases, including chronic pulmonary obstructive disease (COPD) and asthma. Excessive lung inflammation is a prominent feature in disease exacerbations, but the underlying mechanisms remain poorly understood. Cell surface glycoprotein MUC18 (alias CD146 or melanoma cell adhesion molecule) has been shown to promote metastasis in several tumors, including melanoma. We explored the function of MUC18 in lung inflammatory responses to bacteria (eg, Mycoplasma pneumoniae) involved in lung disease exacerbations. MUC18 expression was increased in alveolar macrophages from lungs of COPD and asthma patients, compared with normal healthy human subjects. Mouse alveolar macrophages also express MUC18. After M. pneumoniae lung infection, Muc18−/− mice exhibited lower levels of the lung proinflammatory cytokines KC and TNF-α and less neutrophil recruitment than Muc18+/+ mice. Alveolar macrophages from Muc18−/− mice produced less KC than those from Muc18+/+ mice. In Muc18−/− mouse alveolar macrophages, adenovirus-mediated MUC18 gene transfer increased KC production. MUC18 amplified proinflammatory responses in alveolar macrophages, in part through enhancing the activation of nuclear factor-κB (NF-κB). Our results demonstrate, for the first time, that MUC18 exerts a proinflammatory function during lung bacterial infection. Up-regulated MUC18 expression in lungs (eg, in alveolar macrophages) of COPD and asthma patients may contribute to excessive inflammation during disease exacerbations.